A comparison of test duration for the clinical diagnosis of pediatric tuberculosis using Tuberculin Skin Test (TST) and Interferon Gamma Release Assays (IGRA) - Olivianto, Ery; Iskandar, Agustin; Akmaly, Triyana Dian Dhuha; Mirza, Sarah Zoraya; Jahono, Maxie Felix (Pediatric Sciences Journal, 2025)
Background: Tuberculosis (TB) remains a major global health challenge, particularly among children. Diagnosing pediatric TB is complicated due to nonspecific symptoms and the difficulty of obtaining sputum samples for microbiological confirmation. Immunological tests, such as the tuberculin skin test (TST) and interferon-gamma release assays (IGRAs), are commonly used to support diagnosis. However, TST has several limitations, including the need for multiple patient visits and potential cross-reactivity with Bacillus Calmette-Guérin (BCG) vaccination. This study aimed to compare the efficiency of IGRA and TST in terms of turnaround time and patient compliance. Methods: A diagnostic time comparison study was conducted in pediatric patients with suspected pulmonary or extrapulmonary TB at Saiful Anwar Hospital, Malang. Patients underwent both TST and IGRA testing. The time required to obtain results and patient compliance was recorded and analyzed. o Results: A total of 94 pediatric patients were included, with 17 diagnosed with extrapulmonary TB and 77 with pulmonary TB. IGRA demonstrated a significantly shorter turnaround time (25.43 ± 6.31 hours for pulmonary TB, and 25.58 ± 6.37 hours for extrapulmonary TB) compared to TST (50.16 ± 6,93 hours for extrapulmonary TB and 50.34 ± 7.16 hours for pulmonary TB). Additionally, IGRA provided higher positivity rates in both pulmonary and extrapulmonary TB cases. Conclusion: IGRA offers a faster and more convenient alternative to TST for diagnosing pediatric TB. Despite its higher cost, the efficiency and single-visit requirement of IGRA makes it a preferable diagnostic tool in clinical settings, especially for children suspected of having TB.